2014
DOI: 10.1097/ccm.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapeutic Strategies on the Prognosis of Candidemia in the ICU*

Abstract: Candidemia in ICU patients is caused by non-albicans species in 48% of cases, C. parapsilosis being the most common among these. Overall mortality remains high and mainly related with host factors. Prompt adequate antifungal treatment and catheter removal could be critical to decrease early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
80
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 45 publications
8
80
2
5
Order By: Relevance
“…Although the ideal time for starting antifungal drugs is not yet known, previous studies have found correlations between worse prognosis and delays in the initiation of antifungal therapy and inadequate empirical antifungal therapy. (11)(12)(13)26,27) These studies and our findings suggest that early antifungal administration is key. Lastly, the number of patients (10/16 patients, 62.5%) for whom CVC was removed or exchanged within 48 hours of collection of blood culture sample was too low to have reduced hospital death in our study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Although the ideal time for starting antifungal drugs is not yet known, previous studies have found correlations between worse prognosis and delays in the initiation of antifungal therapy and inadequate empirical antifungal therapy. (11)(12)(13)26,27) These studies and our findings suggest that early antifungal administration is key. Lastly, the number of patients (10/16 patients, 62.5%) for whom CVC was removed or exchanged within 48 hours of collection of blood culture sample was too low to have reduced hospital death in our study.…”
Section: Discussionmentioning
confidence: 49%
“…This is important, as numerous studies have demonstrated that catheter removal is important to lower mortality that is associated with candidaemia. (8,11,26) There are some limitations associated with the present study. As a retrospective study, it involved a single centre and had a small sample population.…”
Section: Discussionmentioning
confidence: 99%
“…Attributable mortality due to Candida spp. infections ranges from about 42 to 63% (4,5). Several observational studies described a strict correlation between an early adequate antifungal treatment and reduced mortality in critically ill patients with fungal infections (6,7).…”
mentioning
confidence: 99%
“…rompt, appropriate, first-line antifungal treatment has been shown to improve outcomes in patients with fungemia, but identification is often delayed by the need for subculture from positive blood cultures (1,2). Mass spectrometry (MS) techniques based on matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) technology have made it possible to identify species directly from positive blood cultures (3).…”
mentioning
confidence: 99%
“…We used 61 strains formerly isolated in the context of invasive fungal infection (stored at -80°C) and previously identified by MALDI-TOF MS. These strains were representative of 12 species commonly implicated in fungemia: Candida albicans (15), Candida glabrata (9), Candida parapsilosis (7), Candida kefyr (6), Candida krusei (6), Candida tropicalis (7), Cryptococcus neoformans (4), Candida dubliniensis (3), Candida utilis (1), Candida guilliermondii (1), Candida inconspicua (1), and Saccharomyces cerevisiae (1). Six were isolated directly from blood cultures from patients.…”
mentioning
confidence: 99%